"A language not of this world": Depersonalization and Unintelligibility in Robert Bolaño's "The Part about the Crimes". Issue 1 (2nd January 2021) - Tocco, Fabricio
Abstract : The following article deals with the intersections of the linguistic, the literary, and the political in Roberto Bolaño's "The Part about the Crimes", the fourth chapter of his novel 2666 . Building on Italian philosopher Roberto Esposito, Argentinean anthropologist Rita Segato, and American scholar David Kurnick, I propose that Bolaño engages with what I call "symbolic unintelligibility", using it to respond to literary tradition and to the political conflicts of our times.